Blood Pressure After Endovascular Thrombectomy and Outcomes in Patients With Acute Ischemic Stroke: An Individual Patient Data Meta-analysis. (18th January 2022) - Katsanos, Aristeidis H.; Malhotra, Konark; Ahmed, Niaz; Seitidis, Georgios; Mistry, Eva A.; Mavridis, Dimitris; Kim, Joon-Tae; Veroniki, Areti Angeliki; Maier, Ilko; Matusevicius, Marius; Khatri, Pooja; Anadani, Mohammad; et al.
Abstract : Background and Objectives: To explore the association between blood pressure (BP) levels after endovascular thrombectomy (EVT) and the clinical outcomes of patients with acute ischemic stroke (AIS) patients with large vessel occlusion (LVO). Methods: A study was eligible if it enrolled patients with AIS >18 years of age with an LVO treated with either successful or unsuccessful EVT and provided either individual or mean 24-hour systolic BP values after the end of the EVT procedure. Individual patient data from all studies were analyzed with a generalized linear mixed-effects model. Results: A total of 5, 874 patients (mean age 69 ± 14 years; 50% women; median NIH Stroke Scale score on admission 16) from 7 published studies were included. Increasing mean systolic BP levels per 10 mm Hg during the first 24 hours after the end of the EVT were associated with a lower odds of functional improvement (unadjusted common odds ratio [OR] 0.82, 95% confidence interval [CI] 0.80–0.85; adjusted common OR 0.88, 95% CI 0.84–0.93) and modified Rankin Scale score ≤2 (unadjusted OR 0.82, 95% CI 0.79–0.85; adjusted OR 0.87, 95% CI 0.82–0.93) and a higher odds of all-cause mortality (unadjusted OR 1.18, 95% CI 1.13–1.24; adjusted OR 1.15, 95% CI 1.06–1.23) at 3 months. Higher 24-hour mean systolic BP levels were also associated with an increased likelihood of early neurologic deterioration (unadjusted OR 1.14, 95% CI 1.07–1.21; adjusted OR 1.14, 95% CI 1.03–1.24) and a higher odds of symptomatic intracranial hemorrhage (unadjusted OR 1.20, 95% CI 1.09–1.29; adjusted OR 1.20, 95% CI 1.03–1.38) after EVT. Discussion: Increased mean systolic BP levels in the first 24 hours after EVT are independently associated with a higher odds of symptomatic intracranial hemorrhage, early neurologic deterioration, 3-month mortality, and worse 3-month functional outcomes.